Family Businesses in the Arab World Governance, Strategy, and Financing. - Basly, Sami (Contributions to management science, 2017)
This book focuses on topics such as the cultural specificity of Arab family businesses with regard to shaping their governance and management; the influence that specific values in the Arab world could exert on the management of family businesses; how spiritual and religious values influence business in Arab family firms; and the role of emotions in the management of family firms in the Arab World. Presenting a collection of contributions addressing management, finance, strategy and succession in Arab Family businesses, this book constitutes a novel and unique contribution to the research field of family businesses.